Myogenesis gone awry: the role of developmental pathways in rhabdomyosarcoma - Gustafson, Annika L.; Durbin, Adam D.; Artinger, Kristin B.; Ford, Heide L. (Frontiers in Cell and Developmental Biology, 2025)
Rhabdomyosarcoma is a soft-tissue sarcoma that occurs most frequently in pediatric patients and has poor survival rates in patients with recurrent or metastatic disease. There are two major sub-types of RMS: fusion-positive (FP-RMS) and fusion-negative (FN-RMS); with FP-RMS typically containing chromosomal translocations between the PAX3/7-FOXO1 loci. Regardless of subtype, RMS resembles embryonic skeletal muscle as it expresses the myogenic regulatory factors (MRFs), MYOD1 and MYOG. During normal myogenesis, these developmental transcription factors (TFs) orchestrate the formation of terminally differentiated, striated, and multinucleated skeletal muscle. However, in RMS these TFs become dysregulated such that they enable the sustained properties of malignancy. In FP-RMS, the PAX3/7-FOXO1 chromosomal translocation results in restructured chromatin, altering the binding of many MRFs and driving an oncogenic state. In FN-RMS, re-expression of MRFs, as well as other myogenic TFs, blocks terminal differentiation and holds cells in a proliferative, stem-cell-like state. In this review, we delve into the myogenic transcriptional networks that are dysregulated in and contribute to RMS progression. Advances in understanding the mechanisms through which myogenesis becomes stalled in RMS will lead to new tumor-specific therapies that target these aberrantly expressed developmental transcriptional pathways.